An observer-based blade-pitch controller of wind turbines in high wind speeds. (January 2017) - Corradini, M.L.; Ippoliti, G.; Orlando, G.
Abstract: The paper focuses on variable-rotor-speed/variable-blade-pitch wind turbines operating in the region of high wind speeds, where blade pitch and generator torque controllers are aimed at limiting the turbine's energy capture to the rated power value. Coupled design is described of an observer-based blade-pitch control input and a generator torque controller, both of which not requiring the availability of wind speed measurements. Closed loop convergence of the overall control system is proved. The proposed control solution has been validated on a 5-MW three-blade wind turbine using the National Renewable Energy Laboratory (NREL) wind turbine simulator FAST (Fatigue, Aerodynamics, Structures, and Turbulence) code. Abstract : Highlights: Variable speed/pitch wind turbines operating with high wind speeds are addressed. An observer based blade-pitch controller is proposed tracking the rated power. The control system does not require feedback measurements of wind speed. Closed-loop convergence of the overall control system is theoretically proved. Testing on 3-blade NREL 5 MW wind turbine with FAST code simulator.